2015
DOI: 10.1007/s12289-014-1215-6
|View full text |Cite
|
Sign up to set email alerts
|

Wear behaviour of PVD coated and cryogenically treated tools for Ti-6Al-4V turning

Abstract: Titanium alloys, mainly because of their poor thermal conductivity, need to be cut at relatively low cutting speeds, with obvious negative consequences on the profitability of machining. An important amount of research has been done in order to increase productivity in titanium machining operations: high performance coatings and innovative technologies to improve insert resistance to wear represent promising solutions. In this work, a highly performing cutting insert (coated with a TiAlN layer obtained by Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Moreover, the use of nanocomposite coatings and multi-layered coatings has resulted in improved performance of cutting tools while machining titanium alloys. 4451…”
Section: Tool Life Improvement In Ti6al4v Machiningmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the use of nanocomposite coatings and multi-layered coatings has resulted in improved performance of cutting tools while machining titanium alloys. 4451…”
Section: Tool Life Improvement In Ti6al4v Machiningmentioning
confidence: 99%
“…The treatment is also utilized before and after the surface coatings and has resulted in increasing adhesion and life of cutting tool. 47,5266…”
Section: Tool Life Improvement In Ti6al4v Machiningmentioning
confidence: 99%
“…Deep cryogenic treated tool delivered an outstanding performance compared to the uncoated and untreated tool. Strano et al [11] studied the wear behaviour of PVD coated and cryogenically treated tools during turning of Ti6Al-4V. The results revealed that deep cryogenic treated inserts outperformed untreated inserts at high cutting speed regarding flank wear due to the enhancement of wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It showed that cryogenic treated inserts have better surface finish and less flank wear than untreated inserts. Matteo Strano et al [16] studied the wear behavior of PVD coated and cryogenically treated tools for Ti-6Al-4V turning and found that cryogenic treatment improves tool life in high rate machining of titanium.…”
Section: Introductionmentioning
confidence: 99%